Developing an online health intervention for young gay and bisexual men. - Pachankis, John E; Lelutiu-Weinberger, Corina; Golub, Sarit A; Parsons, Jeffrey T (AIDS and behavior, 2013)
Young gay and bisexual men continue to experience increases in HIV incidence in the US highlighting a need for competent health services, while the prominence of the internet in their social and sexual lives calls for novel preventive modalities. Toward this goal, we adapted an efficacious in-office HIV risk reduction intervention for online delivery. This paper describes the development of the online intervention and highlights the results of interviews and focus groups with the original intervention participants regarding effective adaptation and online delivery recommendations. The final intervention incorporates strategies for overcoming barriers to online intervention with this population and capitalizes on the unique strengths of online intervention delivery. The systematic process described in this paper can be used as a template for other researchers to develop online risk reduction programs and fills an important gap in the field's ability to maximally reach a critical risk group.
Keywords: Adolescent; Adult; Bisexuality; Consumer Health Information; Directive Counseling; Educational Status; Focus Groups; Health Knowledge, Attitudes, Practice; Health Promotion; HIV Seropositivity; Homosexuality, Male; Humans; Internet; Male; Patient Acceptance of Health Care; Patient Satisfaction; Preventive Health Services; Program Development; Prospective Studies; Questionnaires; Risk Reduction Behavior; Risk-Taking; Social Networking; Substance-Related Disorders; Text Messaging; United States